Do penguins care about their neighborhood? Population implications of bioerosion in Magellanic penguin, Spheniscus magellanicus, at Martillo Island, Beagle Channel, Argentina - Scioscia, Gabriela (2024)
Intrinsic and extrinsic factors, such as bioerosion at nesting sites, regulate populationdynamics and are relevant for the long-term conservation of penguins. Colony trends(between 2004–2022) were studied in a Magellanic penguin colony on Martillo Island, Beagle Channel, Argentina and compared between zones with contrasting degrees of erosion(high, medium, low). Individuals from each zone were characterized for foraging ecology,stress, and reproductive performance during the 2017–2018 breeding season to betterunderstand the colony dynamics. Changes in nest abundance varied in magnitude betweennesting zones with different characteristics of occupation time, density and erosion.Declines in nest abundance in the densest, most eroded and longest occupied zone suggests that environmental degradation may be limiting the colony’s carrying capacity. Ahigher percentage of late breeders (probably younger breeders) occupied the less erodedand more recently occupied zone. Foraging, breeding and stress barely differed betweenzones. New individuals recruiting into the breeding colony select less-eroded zones, eitherto reduce competition for nests or to avoid other effects of erosion and high-density areas. Ifthis is the mechanism behind the shift in numbers throughout the island, we expect theisland to be progressively occupied to the west. If competition or other density dependentfactors are at play, a time will come when the vacant east side will begin to be recolonizedby younger individuals. However, if erosion or other long-term effects spread throughout theisland, recolonization may not occur and the colony may ultimately be abandoned as individuals search for new breeding grounds. Erosion at the breeding site may be a key factor inregional population trends of this burrow nesting species, by following an extinction / colonization of new sites process.